Solution viscosity and flocculation characteristics of linear polymeric flocculants in various media - Chimamkpam, T.O. (2011)
Rheological characteristics of linear copolymers of acrylamide (AM) and acryloyloxyethyltrimethyl ammonium chloride (Q9), differing in molar mass and chemical composition, have been studied in distilled water (DW) and industrial water (IW) obtained from a paper mill. For all copolymers, the shear viscosity, ,wasmuch lower as the ionic strength of the water increased, with near Newtonian behaviour observed at high ionic strengths. In DW, the polymer solutions were yield pseudoplastic. Comparison of the behaviour of all flocculants at the same shear rate in the two media was accomplished by modelling the rheological data. The characteristics of the copolymers could be related with their flocculation performance in IW. The rate of flocculation in the IW was generally higher than in the DW. In general, flocculants with higher charge density were effective at lower concentrations exhibiting a lower value for the optimum PEL dosage. The flocculation data were supported with zeta potential measurements. In all cases flocs break under shear with an inability to recover the floc size with time. Overall, the polyelectrolyte behaviour in flocculation as a function of molar mass, charge density and quality of the medium could be correlated. This is of particular importance for papermaking due to the modern tendencies for water closure.